1997
DOI: 10.1080/713756749
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reaching to Grasp: Evidence for Distractor Interference Effects

Abstract: Transport and grasp kinematics were examined in a task in which subjects selectively reached to grasp a target object in the presence of non-target objects. In a variety of experiments significant interference effects were observed in temporal parameters, such as movement time, and spatial parameters, such as path. In general, the presence of non-targets slowed down the reach. Furthermore, reach paths were affected such that the hand veered away from near non-targets in reaches for far targets, even though the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
245
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(277 citation statements)
references
References 42 publications
28
245
4
Order By: Relevance
“…This analysis too yielded a highly significant Target-Distractor Separation ϫ Target Location interaction, F(2, 60) ϭ 6.27, p Ͻ .01. Howard, & Jackson, 1997). According to the visuomotor processing hypothesis, this occurs because advance information regarding the position of the target allows selection of the motor representation of the target and inhibition of the motor representation of the competing distractor before observable behavior begins.…”
Section: Experiments 3: Manipulating Target-distractor Separationmentioning
confidence: 99%
See 3 more Smart Citations
“…This analysis too yielded a highly significant Target-Distractor Separation ϫ Target Location interaction, F(2, 60) ϭ 6.27, p Ͻ .01. Howard, & Jackson, 1997). According to the visuomotor processing hypothesis, this occurs because advance information regarding the position of the target allows selection of the motor representation of the target and inhibition of the motor representation of the competing distractor before observable behavior begins.…”
Section: Experiments 3: Manipulating Target-distractor Separationmentioning
confidence: 99%
“…This spatial repulsion effect-first reported by Fischer and Adam (2001)-adds to previous reports showing hand path deviations caused by the presence of distractors (e.g., . Interestingly, however, hand paths may veer either away or toward distractors (e.g., Tipper et al, 1997;Welsh, Elliott, & Weeks, 1999). Tipper and colleagues postulated a tentative neurophysiological model to explain hand path deviations Tipper, Howard, & Houghton, 2000;Tipper et al, 1997).…”
Section: Spatial Repulsion Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, various studies have demonstrated that the brain not only identifies and encodes information about the target object, but that the neural architecture also takes into account the presence of non-target objects located within the surrounding area (Rice et al 2006;Tipper, Howard & Jackson, 1997;Tresilian, 1998). For example, Tipper, et al, (1997) demonstrated that hand trajectories were affected by the presence of non-target objects, even when such non-target objects did not physically obstruct the path of the hand to the target object. When these items were present in the workspace, the trajectory paths of the reaching hand significantly deviated away from the perceived obstruction.…”
Section: Aim 2: a Comparison Of 3d Depth Cues Across Open-and Closed mentioning
confidence: 99%